PEMBUATAN APLIKASI MONITORING DAN TRACKING BUS TRANS KOETARADJA BERBASIS ANDROID - Ayu Herlinda; ROmy Dharmawan (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2019)
One of the problems that's often faced in the big cities is the traffic jam caused by the growth of vehicles notaccompanied by the widening of the appropriate road and one of the alternatives to reduce congestion is by thepresence of Trans Koetaradja public bus. But the existence of Trans Koetaradja bus can not be detected by prospectivepassengers. Based on that situation trans koetaradja required an android-based system to monitor and mentracking thebus position so that prospective passengers doesn't have wait too long at the bus stop or missed the bus. This researchentitled "Making Applications Monitoring And Tracking Bus Trans Koetaradja Based on Android”. This applicationwill be installed on mobile devices of prospective passengers of Trans Koetaradja bus and the second will be placed onTrans Koetaradja bus. Both of these applications will communicate with each other through the internet and GPS to beable to know the position of Trans Koetaradja bus accurately. This study aims to facilitate the bus users in knowing thebus has arrived or not by using the application and simplify the bus users in managing the time so they don't have spendtoo long waiting for the arrival of the bus by using the application. The research method used in this research isqualitative method that is called analyzing data by collecting, processing and interpreting data so that it can give aclear picture about the condition being researched and then take a decision which ended by drawing some conclusionsand giving suggestions of its nature by helping to improve the deficiencies encountered in the process of preparing astudy. From the test results in the field using this application on 2 pieces of Android Xiaomi Redmi 4x and XiaomiRedmi 3x in the user can detect the existence of the bus and the distance between the user position (user) and the bus ina Maps with a good level of accuracy